Pengembangan Konten Video Youtube “Barzanji Bugis” Sebagai Wujud Pelestarian Kearifan Lokal Sulawesi Selatan - A. Padalia A. Padalia; Baso Indra Wijaya Aziz; M. Muhlis Lugis (Seminar Nasional LP2M UNM, 2021)
Abstract. The research was conducted using a qualitative descriptive method with the aim of providing an explanation of the phenomena that occur in the present, as well as to describe systematically, factually, and accurately about the facts or properties and the relationship between the phenomena studied (Moleong, 2006). The phenomenon that occurs today is that the younger generation in South Sulawesi and especially in Makassar City is able to read barzanji even more so when reading it in the form of lontara bugis script or better known as barzanji bugis. The data collected in this study are primary data and secondary data. The results of primary and secondary data collection in this qualitative study were then analyzed and processed into video content material. The data collection was carried out accompanied by the taking of recordings in the form of audio-visual which later became a documentary video. From the results of video showings given to teenagers aged 18-25 years as many as 62 people, the appreciation obtained included: A total of 82.3% stated that the video duration of 16 minutes 13 seconds was deemed appropriate to present information on the Barzanji Bugis documentary video. The material content presented in the video includes: 1). Barzanji learning for young children in Islamic boarding schools. 2). An introduction to the definition and history of barzanji. 3). Barzanji bugis as a form of preservation of local wisdom of South Sulawesi. 4). The profile of the barzanji bugis activist, Ust. Moh. Khumaidi Ali, SQ., M.Th.I. 5). Barzanji Bugis reading video presentation. Ustadz Khumaidi's performance received a positive appreciation, as many as 54.8% of respondents stated that they were interested in learning barzanji bugis.Keywords: barzanji bugis, youtube, documentary video